If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6n-3n=3n+6
We move all terms to the left:
6n-3n-(3n+6)=0
We add all the numbers together, and all the variables
3n-(3n+6)=0
We get rid of parentheses
3n-3n-6=0
We add all the numbers together, and all the variables
-6!=0
There is no solution for this equation
| -8+5x=-20 | | (3x-2)^2=(5x+1)(5x-1) | | 15y=5y+9 | | 5(t-8)/2=t-5 | | 2.3=-3.2=+x/5 | | X²+6x=1 | | 1.6=b=8 | | 2.3=-3.2=x/5 | | 5x+17=3x+49 | | 9x+8/4+8x-2/3=21 | | 5x^2-8x-40=0 | | 6(n-5)-3n=3 | | 5(x+3)-3x=30 | | 4(n+1)=3(n-1) | | 2x–5=37 | | 2x–5=37. | | 4(x+7)-1=4x+27 | | 0=5+17t-16t^2 | | -4.8f=6.4=-8.48 | | 9(w-7)=-2w+47 | | 2m+3m-1=24 | | -(2-6n)=18+n | | 7-6m-1=24 | | 3x^2+36x+4=0 | | 6(x-1)-2(5x-4)=-10 | | 8(8n-2)=40n+8n | | -1/4(8a+20)=-2a+5 | | 7/8=3x | | 2t-5=-10t | | 7-4(x+1)=9-5x | | 8/3=-4/3+x | | Z=-1-3i |